The Effect of Psychoreligy Dzikir Intervention on Self Efficacy and Blood Pressure on Hypertension - Adivtian Ragayasa; Sylvina Rahmawati; Emdat Suprayitno (Journal Of Nursing Practice, 2022)
Background: Hypertension is a chronic disease condition that causes impaired self-efficacy and increased blood pressure. One of the non-pharmacological therapies that can do is dzikir or dhikr therapy. Purpose: This study aimed to determine the effect of remembrance therapy on self-efficacy and blood pressure in hypertension. The study was an experimental study using a Randomized Pre Test-Post Test Control Group Design in hypertensive patients receiving psycho religious therapy. The subjects in this study were all hypertensive patients in the working area of ??the Teja Pamekasan Health Center, as many as 20 people. Methods: The selected sample in this study was some hypertensive patients taken by simple random sampling. Blood pressure measurements were carried out twice before psycho religious therapy and two weeks after psycho religious therapy. Psychoreligious therapy is a series of dhikr and prayer by saying the letter "Al-Fatihah" 7 times, then "Istighfar" 100 times, followed by solawat "Allahumma shall 'ala Muhammad wa Ali Muhammad" as much as 100 (Solawat "Ya sayyidi ya Rasulullah " as much as 1000 times) which does once every day. Mann Whitney U Test analyzed data. Results: The results of calculations using the Mann Whitney U Test statistical test showed a difference in blood pressure at the time of pre and post. The significance values indicate this at pre and post are 0.002 and 0.005. Conclusion: Psychoreligious therapy in remembrance can increase self-efficacy and reduce blood pressure in hypertensive patients in the elderly posyandu in the working area of ??the Teja Pamekasan Health Center.